ANALYSIS OF EARLY CHILDHOOD DRAWINGS IN KINDERGARTENS PEMBINA RATO VILLAGE SUBDISTRICT LAMBU DISTRICT BIMA - Oktafianingsih Oktafianingsih; Lanta L. Lanta L.; Hasnawati Hasnawati (Universitas Negeri makassar, 2019)
This study aims to provide an objective description of the analysis of early childhood images in kindergarten builders in Rato Village, Lambu Sub-district, Bima District. In collecting data, researchers used observation, interview, and documentation methods. This research uses a content analysis method (content analysis) that is analyzing children's pictures. The subject matter studied in this research is to describe the pictures of early childhood in Pembina Kindergarten of Rato Village, Lambu Sub-district, Bima District. Of the 25 works, there are several kinds of drawings, namely the pattern of the development of children's drawings of the mottled phase period (2-4 years). There are 13 works and the pre-reality period (4-7 years) there are 12 works. Objects drawn by an early childhood in kindergarten Pembina Rato Village Lambu District Bima District in the drawing are natural scenery objects, the environment around the house, animals, plants, and streaks. The result of the research shows that in the whole screw-up period the children's drawings only have meaningless graffiti, ie circle, horizontal, vertical, and curved. There are eight children whose age is already in the period of Prabagan but the image is still classified in the period of the screw-up. In the pre-reality period, the overall result of the child image has already begun to form the desired image object, but the average mastery of space on the child's image can not be mastered, and some children who have mastered the placement of space in the picture. The color used in the drawing is still fixated on the child's wishes and the concept of the shape on the image has not been seen clearly.